Bioscience student’s perspectives & academic performance before, during & after a stability period of COVID-19 - Narnaware, Yuwaraj; Cuschieri, Sarah (My University, 2022)
Findings suggest that nursing students may have counter-balanced the missing active learning strategies of face-to-face learning and adopted self-directed learning during the COVID-19 period through synchronized learning. Virtual, synchronized learning by using a ‘blended, multi-modal & pedagogical’ approach may serve as a “new normal” of teaching and learning of biosciences if pandemics like Covid-19 re-emerge in the future.
Presented June 2022 [Keynote address] at the International Short-Term Training Program-1 on Recent Advances in Environmental Toxicology and Wildlife Conservation at Raj Rishi Government Autonomous College, Alwar, Rajasthan, India.
Keywords: nursing education; virtual learning; synchronized learning; COVID-19